Statistical Test for Evaluation of Impact of Health Risk - Kamsa-ard, Siriporn (Journal of Health Science of Thailand, 2018)
There are several risk factors commonly act together to cause a disease. To get rid of any of them can possibly reduce the incidence of the disease. Focusing only on control of risk factors with impressive strength of associations does not always guarantee efficient outcomes as planned. The best way is to prioritize efforts on removal of relevant risk and using the risk factor to calculate the attributable risk in the population. PAR (Population Attributable Risk) is the products of the attribute risk and the prevalence of exposure to the risk factor in a population. It measures the excess risk of disease due to the exposure in total population. This article explains the concept and method of calculation of PAR and PAF (Population Attributable Fraction), in case of study design cannot lead to a direct calculation of PAR.